Factores que afectan la estructura de recubrimientos de cinc obtenidos por inmersión - Seré, Pablo Ricardo (1998)
Coating solidification during hot-dip galvanizing is very complex due to Al-Fe, Al-Fe- Zn and Fe-Zn intermetallic compounds development. Fe-Zn ones are brittle and detrimental for mechanical properties, while the diffusion towards the surface of a segregated insoluble alloying such as antimonium causes the sheet darkness. Steel sheets of different roughness were hot-dip galvanized under different operation conditions using a laboratory scale simulator. The effect of steel roughness and process parameters upon coating characteristics were analysed Experimental results showed that the steel roughness affects the coating thickness, zinc grain size and texture as well as the out-bursts development, while the process parameters effects the Fe2Al5 morphology and anümonium segregation.